Hermitian Symmetry of a Dynamic Structure with Odd Elasticity - Feng, Z.C. (Journal of Vibration Testing and System Dynamics, 2026)
We present the wing flutter model as a dynamic structure with odd elasticity. The wing flutter model is an elastically supported airfoil in the flow. The lift force contributes to the non-Hermitian stiffness to the existing elastic support. The stability analysis of the flutter model demonstrates the onset of oscillations due to the odd elasticity. Surprisingly, we found linear coordinate transformations such that the equations of motion in the new coordinates are Hermitian: with symmetric mass matrix and symmetric stiffness matrix.